Assessment of sources and geographical focus of forestry-related news in two Nigerian newspaper (2017)
The importance of forests, forest management and related information to human sustainable development cannot be overemphasized. This paper reports the analyses of forestry-related news source and their geographical focus in Guardian and Tribune Newspapers in Nigeria between June, 2009 and May, 2014. Purposive sampling technique was used to select the two National dailies because both have column for environment issues, they are available and their continuous existence for the period of the research, circulation and accessibility were guaranteed. Data were collected from the editions on the days these newspapers have slot for environmental columns and were analysed using descriptive such as percentage, frequency and charts as well as chi-square inferential statistics at α0.05. Guardian reported 76.9% of the articles while Nigerian Tribune reported 30.1% articles. The columnists had the highest percentage as the news source of forestry related issues reported with 29.1% of the articles. Also, the highest percentage of the articles reported was the Global focus on forestry issues with 38.1%. There was a significant relationship between the newspapers and the sources that reported the issues. There was however no significant relationship between the newspapers and the geographical focus of the issues that were reported. It was concluded that there will be a reduction of public attention on forestry news since they are more of global issues than immediate concern. Also, since forestry news were more from columnists, there was likely to be a professional gap, which needed to be filled.